Analyzing the Impact of Corporate Hedging on Enterprise Valuation: Evidence from China - Nasriddinov, Bobur; Kurbonov, Sinbad; Mulbah, Kessellie Traore (European Scientific Journal, ESJ, 2024)
In a dynamic global financial landscape marked by unprecedented turbulence, driven notably by the COVID-19 pandemic, corporate hedging practices emerged as a critical tool for managing risks and preserving enterprise value (EV). This research investigated the intricate relationship between corporate hedging and EV, with a specific focus on Chinese-listed firms spanning the period from 2012 to 2023. Employing an extensive sample of 4,574 Chinese-listed firms, the study leveraged the Generalized Least Squares (GLS) model for its empirical analysis. The findings revealed a statistically significant positive impact of corporate hedging on enterprise value, validating the hypothesis that effective risk management strategies contributed to increased firm valuation. Furthermore, the study introduced crucial moderating variables (enterprise ownership and corporate governance index) and uncovered their effects on the relationship between hedging practices and EV. State-owned enterprises and firms with stronger corporate governance mechanisms exhibited a more pronounced positive association between hedging and EV. Overall, this research advanced theoretical frameworks and provided practical insights for corporate leaders, investors, and policymakers navigating the complexities of risk management in a rapidly evolving economic landscape.